LFV searches by ATLAS and CMS experiments - Luca Fiorini (SciPost Physics Proceedings)
The appearance of lepton-flavour-violating processes in LHC proton-proton collisions is one of the possible ways that new physics beyond the Standard Model could manifest itself. This proceeding summarizes the most recent searches for lepton-flavour-violating processes and tests of lepton flavour universality with the ATLAS and CMS detectors, using proton-proton collisions at a centre-of-mass energy of 13 TeV.